2002
DOI: 10.1088/0957-0233/13/7/314
|View full text |Cite
|
Sign up to set email alerts
|

Cross-correlation analysis for temperature measurement

Abstract: The current work demonstrates an optical technique that utilizes micron-resolution particle image velocimetry (µ-PIV) for temperature measurement. The technique is based on the premise that Brownian motion will cause width-wise broadening of the cross-correlation peak. A correlation-based PIV algorithm detects the magnitude of Brownian particle motion and can be used to determine the temperature of the fluid. Results were obtained using fluorescing (rhodamine 542/612) spherical 700 nm diameter polystyren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 11 publications
(13 reference statements)
1
40
0
Order By: Relevance
“…This can be treated as isotropic stresses to determine the temperature within the flow in a non-intrusive way. This was demonstrated by Hohreiter et al (2002) and Chamarthy et al (2009) for correlation peaks computed from interrogation windows with standard PIV evaluation. First, the influence of the particle image size on the accuracy of the determination of the correlation peak's size and position was investigated.…”
Section: Isotropic Stressesmentioning
confidence: 88%
“…This can be treated as isotropic stresses to determine the temperature within the flow in a non-intrusive way. This was demonstrated by Hohreiter et al (2002) and Chamarthy et al (2009) for correlation peaks computed from interrogation windows with standard PIV evaluation. First, the influence of the particle image size on the accuracy of the determination of the correlation peak's size and position was investigated.…”
Section: Isotropic Stressesmentioning
confidence: 88%
“…Already in 1986, it was realized that turbulent fluctuations will lead to a broadening of the correlation peak in speckle velocimetry, so that the turbulence level can be determined from its width (Arnold et al 1986). As mentioned before, fluctuations due to Brownian motion will also broaden the peak, making it possible to deduce the local temperature from a cross-correlation analysis (Hohreiter et al 2002). Recently, it has been proposed to determine the Reynolds stresses from ensemble-averaged single-pixel PIV by considering the shape of the resultant correlation function shape (Scharnowski et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 shows a typical image of the 500 nm diameter micro-particle seeded flow. During the last 10 years, the μPIV technique has been used in many research fields, for example, to study electroosmotic, pressure driven and mixed flow in a twin-T microchannel intersection [34], thermal measurement dependent Brownian motion of microparticles [35], investigation of fluid slip mechanisms at wall [36] and in hydrophobic microchannels, internal circulation of aqueous plugs in two phases flow [37], in measurements of beads suspensions in water and human blood, using the red blood cells as a natural particle seeding [38]. A comprehensive review on the μPIV technique can be found in [39] and [40].…”
Section: Micro-particle Image Velocimetrymentioning
confidence: 99%